Mathematics lecturers’ views on the teaching of mathematical modelling - Treffert-Thomas, Stephanie; Viirman, Olov; Hernandez-Martinez, Paul; Rogovchenko, Yuriy (NOMAD Nordic Studies in Mathematics Education, 2017)
The paper reports on the views and use of mathematical modelling (MM) in university mathematics courses in Norway from the perspective of lecturers. Our analysis includes a characterisation of MM views based on the modelling perspectives developed by Kaiser and Sriraman (2006). Through an online survey we aimed to identify the main perspectives held in higher education by mathematics lecturers and the underlying rationale for integrating (or not) MM in university courses. The results indicated that most respondents displayed a realistic perspective on MM when it came to their professional practice. There was a more varied response when it came to their views on MM in teaching. Regarding conditions influencing the use or non-use of MM in teaching, these mainly concerned the mathematical content and the institutional practices.